Advancing the Frontiers of Monetary Policy - Adrian, Tobias (International Monetary Fund, 2018)
Contributors working at the International Monetary Fund present 14 chapters on the development of monetary policy over the past quarter century through the lens of the evolution of inflation-forecast targeting. They describe the principles and practices of inflation-forecast targeting, including managing expectations, the implementation of a forecasting and policy analysis system, monetary operations, monetary policy and financial stability, financial conditions, and transparency and communications; aspects of inflation-forecast targeting in Canada, the Czech Republic, India, and the US; and monetary policy challenges faced by low-income countries and how inflation-forecast targeting can provide an anchor in countries with different economic structures and circumstances.